2014
DOI: 10.1155/2014/268789
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Sludge Granulation in a Full-Scale Sequencing Batch Reactor

Abstract: Aerobic granulation of activated sludge was successfully achieved in a full-scale sequencing batch reactor (SBR) with 50,000 m3 d−1 for treating a town's wastewater. After operation for 337 days, in this full-scale SBR, aerobic granules with an average SVI30 of 47.1 mL g−1, diameter of 0.5 mm, and settling velocity of 42 m h−1 were obtained. Compared to an anaerobic/oxic plug flow (A/O) reactor and an oxidation ditch (OD) being operated in this wastewater treatment plant, the sludge from full-scale SBR has mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 49 publications
1
34
0
4
Order By: Relevance
“…The MLSS, SVI 30 and granules diameter were observed to be within the ranges of 2.7-4 g/L, 40-56 mL/g and 0.5-0.6 mm, respectively. This is similar to the values previously reported at this WWTP: SVI 30 47.1 mL/g, diameter 0.5 mm, and settling velocity of 42 m/h (Li et al 2014). Granules were observed to have a well-defined elliptical shape ( Fig.…”
Section: Characteristics Of Agssupporting
confidence: 91%
See 3 more Smart Citations
“…The MLSS, SVI 30 and granules diameter were observed to be within the ranges of 2.7-4 g/L, 40-56 mL/g and 0.5-0.6 mm, respectively. This is similar to the values previously reported at this WWTP: SVI 30 47.1 mL/g, diameter 0.5 mm, and settling velocity of 42 m/h (Li et al 2014). Granules were observed to have a well-defined elliptical shape ( Fig.…”
Section: Characteristics Of Agssupporting
confidence: 91%
“…4a1), which may be due to their affinity for salty and anaerobic conditions. The influent wastewater contains high concentrations of salts (Li et al 2014) and the anaerobic environment of the granules would provide the ideal ecosystem for Planctomycetes. Planctomycetes, Proteobacteria, Acinetobacter and Flavobacterium detection in the AGS, suggested that in addition to producing extracellular polymeric substances favoring granulation they also contributed to the degradation of organic compounds (Adav et al 2008;Jungles et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversion of lab-scale operating reactors to full-scale reactors applied to real scenarios has been accomplished, and Portugal, the Netherlands, South Africa, and China have full-scale batch reactors currently in operation [98]. Advances in this type of technology will benefit the diffusion of its application in the future [99].…”
Section: Biodegradation Studies Of Chiral Drugsmentioning
confidence: 99%